Implementation of IoT Technology in Aquaponics and Modern Aquaculture Systems for Optimizing Catfish Growth - Asep Syaputra; Nanda S.Prawira (Telkom University, 2024)
In the modern era, various systems of agriculture and aquaculture have evolved rapidly. One remarkable innovation is modern aquaponics, a method that is gaining recognition as a sustainable solution for food production. This system combines fish farming and agriculture into a unified and mutually beneficial approach. Modern aquaponics has proven to be effective in overcoming the constraints of urban land, providing a viable solution for both agriculture and aquaculture. For optimal results in fish farming, it is crucial to consistently monitor the conditions of fish growth and health to avoid the risk of crop failure. In response to this challenge, this study aims to implement an Internet of Things (IoT) system in modern aquaponics, focusing primarily on enhancing the growth of catfish in a controlled and efficient manner. This system employs a range of IoT sensors, including pH sensors, Total Dissolved Solids (TDS) sensors, and temperature sensors, to monitor the water quality within the aquaponics setup continuously. Such monitoring not only ensures optimal conditions for healthier fish but also increases plant productivity, thereby enhancing the overall sustainability and effectiveness of the cultivation process. The results of sensor testing revealed a pH value of 7.2, indicating that the water's acidity level is within a balanced and optimal range for supporting the health of catfish. TDS sensor readings showed a value of 300 ppm, suggesting that the concentration of dissolved particles is ideal for the well-being of the fish. Furthermore, temperature measurements from the DS18B20 sensor recorded a water temperature of 28°C, which falls within the optimal range for catfish growth (28–30°C). These conditions create a stable environment that supports the healthy growth of fish in the aquaponics system.